P163 OUTCOMES OF DISTAL PANCREATECTOMY AND SPLENECTOMY DURING 2-STAGE ESOPHAGECTOMY FOR CANCER. (23rd November 2019) - Syllaios, Athanasios; Mpaili, Eustratia; Mpoura, Maria; Meropouli, Antonia; Davakis, Spyridon; Schizas, Dimitrios; Karavokyros, Ioannis; Charalabopoulos, Alexandros; Liakakos, Theodore
Abstract: Aim: The aim of the study was to assess safety, feasibility and outcomes of esophagectomy with distal pancreatectomy and splenectomy for T4a esophageal and esophagogastric junction adenocarcinoma. Background & Methods: From 01/10/2018 to 01/03/2019, three patients were operated in our Unit for adenocarcinoma of the distal esophagus or esophagogastric junction with 2-stage esophagectomy combined with distal pancreatectomy and splenectomy. Records were reviewed and clinicopathological outcomes presented. Results: All patients were males with a mean age of 55 years (Range: 44-64). Two out of three had undergone neoadjuvant chemotherapy. Mean operative time was 420 min. (Range: 360- 480 min.). Mean blood loss was 180 ml (Range: 150-230ml). Mean ICU stay was 2.33 days (Range:1-3 days). Mean length of stay was 20 days (Range: 15-25 days). Postoperative complications observed was pneumonia in n=1. R0 resection was achieved in all patients while positive lymph node ratio was 0.3 (Range: 0- 0.73). Adjuvant chemotherapy was administered in all patients. Conclusion: Two-stage esophagectomy for cancer along with distal pancreatectomy and splenectomy may be safely performed in specialized Upper GI Units offering adequate postoperative clinical and oncological outcomes. Further studies with larger sample size are needed to reach reproducible results.